Review of Medicinal uses, Phytochemistry and Biological Activities of Antidesma laciniatum and A. membranaceum - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Antidesma laciniatum and A. membranaceum are small trees used as traditional medicines in tropical Africa. This extensive literature review synthesizes the information currently available on the medicinal uses, phytochemistry and biological activities of A. laciniatum and A. membranaceum. The university library and electronic search engines such as Google Scholar, Scopus, Web of Science, ScienceDirect, and PubMed were searched for pertinent information on the medicinal uses, phytochemistry, and biological activities of A. laciniatum and A. membranaceum. Traditionally, the species have been used as aphrodisiac, and traditional medicine for cough, kwashiorkor, mouth ulcers, pneumonia, prevent miscarriage, snakebites, stomachache and wounds. Various phytochemicals such as essential oils, isoflavonoid glycosides, phytosterols, benzopyranones, lignin glucosides, megastigmane, phenolics, steroids, squalene, terpenoids, triterpenoids, and tetrahydroisoquinoline alkaloids have been isolated from A. laciniatum and A. membranaceum. In vitro studies have confirmed the biological activities of A. laciniatum and A. membranaceum which, include antimicrobial, antioxidant, antiplasmodial, antitrypanosomal, leishmanicidal, molluscicidal and cytotoxicity activities. More pharmacological studies including phytochemical, toxicological, in vitro and in vivo experiments are needed to provide evidence for the clinical effectiveness of remedies prepared from the species.